Exploring multisensory experiences in infants' learning and development in the child care classrooms. Issue 13 (3rd October 2021) - Shin, Minsun
ABSTRACT: Infants come to know about the world and develop an understanding about themselves through multisenses. This qualitative case study aimed to explore how three infant head teachers engaged in and facilitated various multisensory play activities in their classrooms. Natural, in-class, non-participatory observations were conducted at a child care centre in the U.S. The findings of this study illustrated how the infant teachers in this study provided, promoted, and scaffolded multisensory experiences in their daily practices. The findings also highlighted that the infant teachers adapted sensory experiences to meet individual preferences, needs, interests, and changing developmental status of their infants.